An introduction to infertility counseling: a guide for mental health and medical professionals - Peterson, Brennan; Wischmann, Tewes (Journal of assisted reproduction and genetics, 2012)
The practice of infertility counseling delivered by mental health and medical professionals has become more sophisticated and widespread over the past decade. This paper summarizes information presented at the second campus workshop of the Special Interest Group of Psychology and Counseling of the European Society of Human Reproduction and Embryology (ESHRE). This group is dedicated to improving infertility services by creating meaningful connections between mental health and medical professionals. The paper identifies key issues that infertility counselors must consider in their work with couples experiencing infertility. The use of supportive psychosocial interventions and treatments are highlighted. The paper also details the process for choosing the most appropriate type of infertility counseling, and the use of assessment tools that assist in understanding infertility related symptoms. Infertility counselors should also consider gender differences, the impact of infertility on a couple’s sexual relationship, and the unique challenges couples face regarding third-party conception. Finally, the paper addresses specific recommendations for infertility counselors in mental health and medical settings.